2006
DOI: 10.1063/1.2335390
|View full text |Cite
|
Sign up to set email alerts
|

High electron mobility lattice-matched AlInN∕GaN field-effect transistor heterostructures

Abstract: Room temperature electron mobility of 1170cm2∕Vs is obtained in an undoped, lattice-matched, Al0.82In0.18N∕GaN field-effect transistor heterostructure, while keeping a high (2.6±0.3)×1013cm−2 electron gas density intrinsic to the Al0.82In0.18N∕GaN material system. This results in a two-dimensional sheet resistance of 210Ω∕◻. The high mobility of these layers, grown by metal-organic vapor phase epitaxy on sapphire substrate, is obtained thanks to the insertion of an optimized AlN interlayer, reducing the alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
225
5
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(248 citation statements)
references
References 14 publications
15
225
5
3
Order By: Relevance
“…A thin AlN interlayer between the GaN buffer and the quaternary barrier layer was grown under barrier reactor conditions at about 825°C in all heterostructures to enhance the carrier mobility in the HEMT structures. 7,12 The AlInGaN/ GaN heterostructures of sample series 1 were capped with a thin (12 nm to 36 nm) GaN film for process-relevant issues, as reviewed elsewhere. 8 Rutherford backscattering spectrometry (RBS) using 1.4-MeV He + ions at scattering angle of 170°w as performed to acquire reliable information about the AlInGaN thickness and the exact depthresolved composition.…”
Section: Growth Conditions and Characterization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A thin AlN interlayer between the GaN buffer and the quaternary barrier layer was grown under barrier reactor conditions at about 825°C in all heterostructures to enhance the carrier mobility in the HEMT structures. 7,12 The AlInGaN/ GaN heterostructures of sample series 1 were capped with a thin (12 nm to 36 nm) GaN film for process-relevant issues, as reviewed elsewhere. 8 Rutherford backscattering spectrometry (RBS) using 1.4-MeV He + ions at scattering angle of 170°w as performed to acquire reliable information about the AlInGaN thickness and the exact depthresolved composition.…”
Section: Growth Conditions and Characterization Methodsmentioning
confidence: 99%
“…4,5 Tensilestrained AlInGaN layers with high Al contents and lattice-matched pure AlInN both generate high twodimensional electron gas (2DEG) densities. 6,7 Compressively strained AlInN and AlInGaN layers have been used to generate a piezoelectric polarization which compensates a high spontaneous polarization to lower the 2DEG density and realize e-mode operation. 8,9 However, device performance is limited by the inferior crystal quality caused by the high In content.…”
Section: Introductionmentioning
confidence: 99%
“…It would allow for structures that are both polarization balanced and lattice matched (or the more relaxed strain-balance condition), for instance, by combining Al 82 In 18 N and GaN. 46,47 Since strain is zero, we balance only the spontaneous part of the polarization.…”
Section: B Prospects and Challengesmentioning
confidence: 99%
“…HEMTs with nearly lattice matched AlInN barrier layers were essentially predicted to provide higher carrier densities than in those with an AlGaN barrier layer [8], which is promising for high power and high frequency transistor operations [14]. Gonschorek et al [10] reported a high density of carriers (2.6 × 10 13 cm − 2 ) with the electron mobility of 1170 cm 2 /Vs resulting in a low sheet resistance of 210 Ω/sq at room temperature (RT) for an AlInN/GaN heterostructure. Similarly, Tulek et al [14] reported a very high electron density of 4.23 × 10 13 cm −2 with a corresponding electron mobility of 812 cm 2 /Vs which yielded a record two-dimensional sheet resistance of 182 Ω/sq for heterostructure with an Al 0.88 In 0.12 N barrier layer.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed to improve the performance of devices, such as increasing the Al composition of an AlGaN barrier [2], using a thin AlN spacer layer at the AlGaN/GaN interface [3,4], and replacing the GaN with InGaN as the channel [5,6] and AlGaN with AlInN [7][8][9][10][11][12][13][14][15][16] as the barrier. Among these, the lattice-matched AlInN barrier is considered to be the most promising barrier alternative for improving the HEMT performance.…”
Section: Introductionmentioning
confidence: 99%